Strategi Peningkatan Mutu Tembakau Besuki Na-Oogst di PTPN X Kebun Kertosari Jember - Auliana Chairun Nisa; Rudi Wibowo; M. Rondhi (School of Business, Bogor Agricultural University (SB-IPB), 2017)
PTPN X Kebun Kertosari is a tobacco agribusiness company. In the period of 2010-2014, the quality of tobacco declined annually, and the plantation was unable to achieve its quality target. The objectives of this research are: (1) to identify the causes of failure of the company in achieving its target of Besuki Na-Oogst tobacco, and (2) to identify strategies in improving the working performance of PTPN X Kebun Kertosari. The primary data were collected from observations and focused group discussions while the secondary data were obtained from the company archives of data on production and quality of tobacco. The research method was an analytical descriptive using the data analysis methods of fishbone diagram, Pareto diagram and Analytical Hierarchy Process (AHP). The results showed that factors affecting the quality of the Besuki Na-Oogst tobacco of PTPN X Kebun Kertosari include the human resources, methods, materials, machines and environment. The main cause of degradation of tobacco quality (80%) is labor negligence, and lack of labor skills contributes as much as 26.7%. The alternative strategy prioritized to improve the quality of the performances of the company human resources. The result of the research recommends the company to provide assistance and monitoring to its employees so that negligence and errors in production can be minimized, and the company should focus and pay attention to its human resource quality, thus increasing the performance quality of Besuki Na-Oogst tobacco of PTPN X Kebun Kertosari.Keywords: tobacco besuki Na-Oogst, quality performance, fishbone diagram, pareto diagram, analyticaal hierarchy processABSTRAKPTPN X Kebun Kertosari adalah perusahaan agribisnis komoditas tembakau. Pada tahun 2010-2014 mutu tembakau semakin menurun setiap tahunnya dan tidak mampu mencapai target mutu. Penelitian bertujuan (1) mengetahui penyebab mutu tembakau Besuki Na-Oogst di PTPN X Kebun Kertosari tidak mampu mencapai target dan (2) mengetahui strategi peningkatan kinerja mutu PTPN X Kebun Kertosari. Metode penelitian dilakukan secara deskriptif analitik dengan metode analisis data diagram tulang ikan, diagram pareto dan Analitycal Hierarchy Process (AHP). Hasil penelitian menunjukkan faktor yang memengaruhi mutu tembakau Besuki Na-Oogst di PTPN X Kebun Kertosari mengalami penurunan sehingga tidak mampu mencapai target disebabkan oleh SDM, metode, bahan baku, mesin dan lingkungan. Hasil analisis Pareto menunjukkan penyebab utama 80% penurunan mutu, yaitu kelalaian dan kurangnya keterampilan tenaga kerja (SDM) yang menyumbang 26,7%. Strategi alternatif yang diprioritaskan untuk peningkatan kinerja mutu, yaitu peningkatan kualitas SDM. Hasil penelitian merekomendasikan perusahaan agar melakukan pendampingan dan monitoring terhadap tenaga kerja agar dapat mengurangi kelalaian dan kesalahan proses produksi serta lebih fokus dan memperhatikan kualitas SDM untuk meningkatkan kinerja mutu tembakau Besuki Na-Oogst di PTPN X Kebun Kertosari.Kata kunci: tembakau besuki Na-Oogst, kinerja mutu, diagram tulang ikan, diagram pareto, analisis proses hirarki